Sistem Manajemen Kesenian Jaran Kepang Turonggo Mudo Ngesti Budaya Kabupaten Semarang Sebagai Upaya Eksistensi Seni Tradisi - Laura Andri Retno (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2019)
The material object in this study is the jaran kepang Turonggo Mudo Ngesti Budaya art group located in Semarang Regency. Using the arts management theory and qualitative research methods and in-depth interviews, this study aims to analyze the management system used in the arts group. The data acquisition supports the results of the research, in the form of (1) the planning stage, consisting of weekly, monthly, and incidental work programs carried out by the Turonggo Mudo Ngesti Budoyo art group; (2) organizing stage is the activity of sorting work according to organizational structure and fostering members; (3) the stage of supervision / controlling ,consisting of the introduction, implementation and saving back, and (4) the evaluation stage, namely the stage of evaluation of the success or failure of the activities carried out by the art group. Of the four stages carried out it can be said that the Turonggo Mudo Ngesti Budaya group is a traditional arts group with a good management system, even though the process of regeneration and financial management is not optimal enough, because there is no separation of leaders on the artistic and production sides, even though the selection and management of the right management will make traditional arts groups are more optimal in existence.